Understanding Psychosocial Distress and the Distressing Items on the Distress Thermometer Problem List: A cross-sectional Study from Nepal - Prajapati, Roshan; Thapa, Sudip; Pokhrel, Samikcha; Sharma, Rajeev; Thapa, Pradeep (Annapurna Journal of Health Sciences, 2023)
Introduction: Psychosocial distress is common in cancer patients and there are various risk for it. Unfortunately, the prevalence and risk of psychosocial distress are not uniform within the studies. Understanding the prevalence and risk of psychosocial distress could be an effective for its prevention and management. The objective of this study is to evaluate the prevalence and most distressing items for psychosocial distress. Methods: This descriptive cross-sectional study was done in a tertiary cancer center. A total of 253 heterogeneous cancer patients were enrolled in this study. Information regarding socio-demographic and clinical characteristics, psychosocial distress and source of most distressing problems were collected subjectively. Distress thermometer accompanied with problem checklist described their perceived distress and sources of distressing problems respectively. Descriptive statistics was used to analyze the variables. Statistical analysis was done using SPSS version 20. Results: 51.8% of study cohorts were distressed. Among the problems category, most frequent were physical and emotional domains. The most distressing items were fatigue, worry, financial constraints and family health issue. Conclusion: Psychosocial distress is commonly prevalent among cancer patients. These patients need regular screening and appropriate intervention for psychosocial concerns accordingly. Healthcare professionals should prioritize and address vulnerable issues that could be beneficial for preventing psychosocial distress.